Non-invasive methods in the diagnosis of autoimmune diseases: examples of clinical cases - M. M. Kokhan; N. V. Zilberberg; E. P. Topychkanova; O. G. Rimar; A. A. Patrusheva (Лечащий Врач, 2021)
The article presents the clinical cases of dermatological manifestations of various forms of lupus erythematosus, in the diagnosis of which a modern non-invasive method for the study of lesions «in vivo» was used – Reflectance Confocal Laser scanning Microscopy. As a result, pathological morphological signs of this collagenosis were revealed, which allowed us to suspect the diagnosis of lupus erythematosus at the prebiopsy stage, which was confirmed by the pathomorphological study.